The Position of Women and Women's Rights in Islamic Family Reform: A Comparison in Indonesia and Tunisia - Umi, Umi Khoirun Nisa; Ummil Fadhliyah Soraya; Maryani; Umar Yusuf (Medina-te : Jurnal Studi Islam, 2024)
This research was prepared with the aim of discussing the position and fight for women's rights in the Islamic Family reform (Comparison in Indonesia and Tunisia). Some women demand that their rights be taken away by male hegemony. This theme ultimately falls within the scope of the Holy Quran which is used as a source of legitimization of the relationship between men and women. The research method used in this study is the method of collecting data through library research. Data is collected by gathering information from various sources of literature, including books, magazines, journals, and others. From this research, it can be concluded that the reform of Islamic family law in Indonesia and Tunisia was carried out to answer the needs of the times and especially to raise the degree (status) of women, namely through nurturing, preserving and then fighting for women's rights. Although the minimum standards of marriage and polygamy differ in the two countries, they share a similar principle and goal: the protection of women's rights. Nonetheless, these rights are equivalent by nature in sharia (maqasyid ash-shari'ah), such as the right to mental and psychological health (equivalent to the nature of hifz an-nafs/maintaining the soul), then the right to maintain reproductive health (equivalent to the nature of hifdz al-nasl/maintaining offspring), Furthermore, the right to obtain equal opportunities in the field of education (commensurate with the nature of hifdz al-'aql / preserving the intellect) and the provisions of polygamy between the two countries also have commensurate goals and principles, namely to protect women's honor or human rights (commensurate with the principle of hifdz al-'ird).